Primary healthcare centers engagement in tuberculosis treatment in Ukraine - Geliukh, Evgenia; Nabirova, Dilyara; Davtyan, Karapet; Yesypenko, Svetlana; Zachariah, Rony (The Journal of Infection in Developing Countries, 2019)
Introduction: We assessed the influence of a result-based financing (RBF) model, which included incentives for Primary Healthcare facilities on TB treatment outcomes. Methodology: We compared TB patients > 17 years and their treatment outcomes among those who did and did not benefit from RBF-model in 14 districts of Odeska oblast, Ukraine in 2017. Log-binomial regression was used to examine factors associated with being included in RBF-model. Results: Of 2,269 reported TB patients, 308 (14%) were included in RBF-model. Most patients in the RBF-model were from rural areas 229 (74%), unemployed 218 (71%), and HIV-infected 131 (43%). Individuals from urban areas (Adjusted risk ratio, ARR =0.9, 95% Confidence Interval, CI:0.89-0.94), having drug-resistant TB (ARR = 0.3, 95% CI: 0.18-0.45), and relapse TB (ARR = 0.6, 95% CI:0.40-0.83) were less likely to be included in RBF-model. Favorable outcomes in new/relapse cases with RBF-model was 89% compared with 41% (p < 0.001) without RBF. Similarly, for other retreatment this was 83% versus 40% (p < 0.001). Failures in the no-RBF group was 29% for new and relapse cases while for other retreatment cases, it was 26% (significantly higher than in the RBF-model). Conclusion: RBF-model is effective in achieving high levels of favorable TB treatment outcomes. Almost three-in-ten TB patients in non-RBF category failed TB treatment despite having drug-susceptible TB. Efforts are now needed to include it within ongoing public health reforms and assess the feasibility of scaling-up this intervention through implementation research and dedicated funding.